2017
DOI: 10.1136/bmjsrh-2017-101799
|View full text |Cite
|
Sign up to set email alerts
|

Social media and the intrauterine device: a YouTube content analysis

Abstract: While one-third of IUD user testimonials on YouTube contained inaccurate information, the majority of IUD experiences were perceived by our study viewers to be positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 18 publications
5
24
0
3
Order By: Relevance
“…14 A body of literature has demonstrated that social networking sites may be an important means by which this population obtains information about contraceptive options and sexual health. Specifically, studies show that people post about their experiences with intrauterine devices (IUDs), 15 emergency contraception, 16 and miscarriage. 17 Users request diagnoses for sexually transmitted infections on social media sites, 18 and adolescents exposed to sexual risk reduction messaging on social media-compared with television, school, friends, or parents-are more likely to use contraception.…”
Section: Introductionmentioning
confidence: 99%
“…14 A body of literature has demonstrated that social networking sites may be an important means by which this population obtains information about contraceptive options and sexual health. Specifically, studies show that people post about their experiences with intrauterine devices (IUDs), 15 emergency contraception, 16 and miscarriage. 17 Users request diagnoses for sexually transmitted infections on social media sites, 18 and adolescents exposed to sexual risk reduction messaging on social media-compared with television, school, friends, or parents-are more likely to use contraception.…”
Section: Introductionmentioning
confidence: 99%
“…People increasingly rely on the internet as a primary source of health information [13,14]. As part of this trend, researchers have begun to investigate people's health-seeking strategies and the information available online for a wide range of reproductive health needs [10,[15][16][17][18][19][20]. An analysis of videos on YouTube allows us to examine the demographic characteristics of people who attempt self-removal of LARC outside of the clinic setting-data that was not available in previous studies [10,11,21].…”
Section: Introductionmentioning
confidence: 99%
“…(2016; [ 79 ]) Twitter Quantitativ computational 1 54 McBean (2014; [ 80 ]) YouTube Qualitativ Laien + 1 55 McLaughlin et al. (2016; [ 81 ]) Twitter Quantitativ manuell Profis Laien Sonstige 1 56 Miller (2017; [ 82 ]) YouTube Quantitativ manuell Laien + 1 57 Miller (2019; [ 83 ]) YouTube Qualitativ Laien + 1 58 Morris und Anderson (2015; [ 84 ]) YouTube Qualitativ Laien + 1 59 Nguyen und Allen (2018; [ 85 ]) YouTube Quantitativ manuell Laien + 1 60 Nobles et al. (2020; [ 86 ]) Instagram Quantitativ computational 2 61 Onanuga (2020; [ 87 ]) Twitter Qualitativ Laien 1 …”
Section: Methodementioning
confidence: 99%
“…3). Beispielsweise ist untersucht worden, wie die Impfung gegen humane Papillomviren (HPV) auf YouTube [48] und Twitter [79] dargestellt wird (Themengebiet HIV/STI), wie Trans*Personen auf YouTube ihre sexuelle Gesundheit beschreiben [91] und welche alternativen Männlichkeitsbilder auf YouTube [84] vermittelt werden (Themengebiet geschlechtliche und sexuelle Identitäten), wie Mädchen und Frauen sexuelle Gewalt auf YouTube [59] behandeln und welche Möglichkeiten der sexuellen Gewaltprävention auf Twitter [64] diskutiert werden (Themengebiet sexuelle Gewalt), welche Verhütungsinformationen auf YouTube [85] verfügbar sind (Themengebiet Fruchtbarkeit und Verhütung), welche Informationen zu erektiler Dysfunktion auf YouTube [57] oder zu Unfruchtbarkeit auf Instagram und Twitter [44] verbreitet werden (Themengebiet sexuelle und reproduktive Störungen) und welche Informationen über lesbische Lebensweisen [80] oder sexuelle Techniken [33] auf YouTube zu finden sind (Themengebiet sexuelle Funktionen, Lebensstile und Vergnügen).…”
Section: Themen Und Wissensformen Der Sexuellen Gesundheitsinformationenunclassified